PEMBIAYAAN USAHA BUDIDAYA IKAN AIR TAWAR DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Rheza Hermawan; Moh. Huzaini; Akhmad Jufri (Jurnal Adz-Dzahab: Jurnal Ekonomi dan Bisnis Islam, 2022)
The purpose of this study is to explain the implementation of freshwater fish farming business financing from the perspective of Islamic Economics. This research was conducted in Pringgarata District, Central Lombok Regency, West Nusa Tenggara Province. This research is a qualitative research with an explanatory method. Based on field research, there are three forms of financing used by freshwater fish farming business actors from an Islamic economic perspective in Pringgarata District, namely by qardh, syirkah 'inan and mudharabah contracts. Implementation of the pillars and conditions on business financing carried out by freshwater fish farming business actors in Pringgarata District, namely: 1) Qardh contract, the implementation of all the pillars and conditions in the qardh contract is in accordance with the perspective of Islamic economics. 2) Syirkah 'inan contract; a) The first type of cooperation, the implementation of conditions for capital contribution and loss sharing is not in accordance with the Islamic economic perspective. b) The second type of cooperation, the implementation of conditions for capital contribution, profit sharing and loss sharing are not in accordance with the Islamic economic perspective. 3) Mudharabah contract, the implementation of the terms of profit sharing is not in accordance with the Islamic economic perspective. Tujuan penelitian ini yaitu untuk menjelaskan implementasi pembiayaan usaha budidaya ikan air tawar yang ditinjau dari persepektif ekonomi Islam. Penelitian ini dilakukan di Kecamatan Pringgarata Kabupaten Lombok Tengah Provinsi Nusa Tenggara Barat. Penelitian ini termasuk ke dalam penelitian kualitatif dengan metode ekpslanatif. Berdasarkan penelitian lapangan terdapat tiga bentuk pembiayaan yang digunakan oleh pelaku usaha budidaya ikan air tawar yang ditinjau dari perspektif ekonomi Islam di Kecamatan yaitu dengan akad qardh, syirkah ‘inan dan mudharabah. Implementasi rukun dan syarat pada pembiayaan usaha yang dilakukan oleh pelaku usaha budidaya ikan air tawar di Kecamatan Pringgarata yaitu: 1) Akad qardh, implementasi semua rukun dan syarat yang ada dalam akad qardh telah sesuai dengan perspektif ekonomi Islam. 2) Akad syirkah ‘inan; a) Jenis kerjasama pertama, implementasi syarat kontribusi modal dan pembagian kerugian belum sesuai dengan perspektif ekonomi Islam. b) Jenis kerjasama kedua, implementasi syarat kontribusi modal, pembagian keuntungan dan pembagian kerugian belum sesuai dengan perspektif ekonomi Islam. 3) Akad mudharabah, implementasi syarat pembagian keuntungan belum sesuai dengan perspektif ekonomi Islam.